The Student-Led Groups Program Model of Practice Education: Pilot Evaluation from the Perspective of Service Provider and University Stakeholders - Freyr Patterson; Anne-Maree Caine; Nadine Ninness; Janelle Griffin; Jennifer Fleming
Background: There is a need for innovative models of student practice placements to accommodate increasing numbers of occupational therapy students while providing quality learning experiences. The Student-Led Groups Program model is a new approach, which involves multiple students in continuous overlapping placements taking responsibility for leading a group program. Aims: The aim of this study was to explore service provider and university stakeholder perceptions of the Student-Led Groups Program model of professional practice education in a brain injury rehabilitation unit. Method: A participatory action research approach was utilised and this paper presents the findings from the first cycle of research. Data were collected using focus groups with service provider and university stakeholders and analysed using a qualitative descriptive approach. Results: Five key themes emerged in the data analysis, 1) positive practice placement experience for students, 2) positive practice placement model for clinicians, 3) improved occupational therapy services for patients, 4) essential components of the program, and 5) wider influence and reach. Conclusions: Findings indicated that the Student-Led Groups Program model was effective in providing quality student experiences and enhanced patient services in an inpatient setting from the perspectives of service providers and university representatives. Recommendations for subsequent research cycles are presented.